Identification of plant growth promoting rhizobacteria from Suaeda nudiflora plant and its effect on maize - Jha, Yachana; Subramanian, RB; Jethwa, Rajesh; Patel, Neha (Indian Journal of Plant Protection, 2020)
Plant growth promoting rhizobacteria (PGPR) are known to influence plant growth by various direct or indirectmechanisms. In search of efficient PGPR strain with multiple activities, two isolates of Pseudomonas and Bacilluswere isolated from rhizospheric soil and root of salt tolerant plant, Suaeda nudiflora, wild mosques. These testisolates were biochemically characterized for their plant growth promoting traits like production of siderophore,phytohormones, volatile compounds, phosphate solubilization, and production of antibiotics and pathogenesisrelated proteins. The biocontrol assay of these isolates also showed good response in maize against Aspergillusniger.